Review on the techno‐commercial aspects of wind energy conversion system. Issue 14 (20th September 2018) - Chatterjee, Shantanu; Chatterjee, Saibal
Abstract : This study provides an overview of the different techno‐commercial aspects of a wind energy conversion system. The review includes the grid codes provided by the transmission system operator of different countries supplemented by various communication protocols, explanation of different types of conventional and advanced wind generators, discussions on different maximum power point algorithms along with various conventional and advanced pitch angle control systems. The study also describes a variable speed system using different types of power electronic converters at the generator and the grid side to maintain power quality, grid synchronisation and unity power factor operation along with various cooling techniques utilised. In a subsequent part, a clear overview of different control topologies such as field‐oriented control, direct torque control, voltage‐oriented control and direct power control has been provided along with the recent advancement of each and every topology. The study also provides the challenges of the prevailing technology along with the already available and possible ways of minimising these technological gaps. Finally, a techno‐commercial comparison of different commercially available wind systems by different companies has been presented along with their market share based on the current scenario.